If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8y + 13 = 0 Reorder the terms: 13 + 3x + 8y = 0 Solving 13 + 3x + 8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + 3x + -13 + 8y = 0 + -13 Reorder the terms: 13 + -13 + 3x + 8y = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 3x + 8y = 0 + -13 3x + 8y = 0 + -13 Combine like terms: 0 + -13 = -13 3x + 8y = -13 Add '-8y' to each side of the equation. 3x + 8y + -8y = -13 + -8y Combine like terms: 8y + -8y = 0 3x + 0 = -13 + -8y 3x = -13 + -8y Divide each side by '3'. x = -4.333333333 + -2.666666667y Simplifying x = -4.333333333 + -2.666666667y
| 3x^2-12x=-9 | | y=6x-3.5 | | -5(1+4x)+1=x+38 | | -5(3p-3)-5(3-3p)=-4p-5p | | x^2+42-135=0 | | t+2=26-2t | | 30=x/7-20 | | 3(4x+4)=6(x+1)+4x | | 34+2n=8(n+5) | | 9x-(5x+9)=4x-24 | | -1/4=2.4x+10-0.35x | | 6x+7=103 | | 3x-3x=-4x | | b-2=b+6+2-10 | | x-3-8x=-24 | | 1/2(-2x-7)=3/4 | | 2x-15=3-x | | cosx^2-cosx=0 | | 8(1+5k)=8(1-7k) | | y=(-13/16)-1/4 | | 6(5x-6)=6(6x+8) | | 4y-3=2y-11 | | -3(4x-7)+3=5x-27 | | 12x+2+7x=1-8x+16 | | m^2+mn+n^2=0 | | 2(2l+w)=72 | | 28-7r=3(1+6r) | | x^4+x^3-x-3=0 | | 35-9= | | 15+2n=29 | | -6n+14=-8n-5n | | 14w^3-33w^2+18w=0 |